Yield Performance and Factor Analysis for Superior Cultivars Identification in Wheat (Triticum aestivum L.) - Kamran, Muhammad; Inamullah, Dr; Iqbal, Muhammad Sajjad (PSM Biological Research, 2016)
The purpose of our study was to differentiate the varieties of wheat depending on their morphological traits relating to yield and to estimate those factors which are responsible for the highest yield plant -1. The 26 different types of local wheat varieties were grown in the field conditions of Hazara University Mansehra, seeded in a Randomized Complete Block Design (RCBD) with 3 replications. Some of the Morphological traits were significant namely, spike length, flag leaf area, awn length, grains per spike, spikelets per spike, number of tillers, peduncle length, grains weight, and grain yield but others were non-significant such as, leaf angel, days to headings, days to maturity, plant height and harvest index. Kaghan-93 (7.77g plant-1) was seen to be the highest production of yield and was observed best within 26 varieties. Factors examination exposed 5 essential factors that estimated 73.24% of the total differences, depending on principal component processes. One of these was awn length that seems to be 18.83% in the direction of the yield. While the second and third component were (16.38%) and (14.53%) for yield component and plant architecture respectively. The fourth factor was the growth factor which was estimated upto 12.86% and maturity parameters was 10.26%. Depending on these factors selection will be conducive to use highest yield genotypes and are suggested for further crop renovation programs.